Unconvential History: Gay, Lesbian, Biseks, Transseksual / Transjender, dan Questioning (GLBTQ) dalam Sejarah Kontemporer Islam. - Awalia Rahma (Fakultas Adab dan Humaniora, UIN Syarif Hidayatullah Jakarta, Indonesia, 2006)
Having penetrated by postmodernism during the past two decades, conventional historiography has yet to face another penetrartion from cultural turn recently. The later, taking form as unconventional history, attarcks more historians to write history in various manner. This paper, however, propose internet as alternative source of history while groups of the most marginalized Muslim, GLBTQ people, apperas as its focal point of view. Both source and issue addressed in its historical explanation are expected to convey untouch area thus makes contemporary historiography more colorful.